Peran Digital Marketing dan Penetaapan Harga Terhadap Keputusan Pembelian Konsumen di Platform E-Commerce Tiktok Shop - Lastri Novita Aplugi; Haryo Kusumo; Tantik Sumarlin (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2026)
This study analyzes the influence of digital marketing and pricing on consumer purchasing decisions on the e-commerce platform TikTok Shop in Semarang Regency, Central Java. The quantitative method was chosen, collecting data from questionnaires and analyzing using SmartPLS 4.0. The study findings indicate that the independent variable, digital marketing, pricing, has a positive and significant effect on the dependent variable, purchasing decisions.